Title: The Comparison of Anxiety Sensitivity and Happiness in Irritable Bowel Syndrome Patients with Normal Matched Group in Shiraz (Fasa University of Medical Sciences, 2012)
Background & Objective: The purpose of this study was the comparison of anxiety sensitivity and happiness between patients with Irritable Bowel Syndrome (IBS) and normal matched group. Materials & Methods: The Subjects were 35 (21 females and 14 male) IBS patients diagnosed by gastroenterologist and 35 (25 female and 10 males) normal matched group all in 14- 63 old age. Anxiety Sensitivity Index (ASI-R), Oxford Happiness Questionnaire (OHQ), and a checklist applied as measures of anxiety sensitivity, happiness and demographic information. Results: Data analysis indicates that IBS patients significantly are higher than matched group in fear of publicly observable symptoms (P= 0.032), fear of cardiovascular symptoms (P= 0.01), fear of gastrointestinal symptoms (P= 0.001), fear of dissociative and neurological symptoms (P= 0.018), & general anxiety sensitivity (P= 0.003), and lower in joy (P= 0.005), control (P= 0.008), self- esteem (P= 0.001) calm (P= 0.006) and general happiness (P= 0.001). Although no significant differences were found in life satisfaction (P= 0.083) & efficacy (P= 0.09), fear of respiratory symptoms (P= 0.067), and fear of cognitive control deficiency (p= 0.097). Conclusion: As a psychological variable anxiety sensitivity can predict treatment seeking of IBS patient, and happiness negatively influenced by both anxiety sensitivity and IBS.